Semen Sojae Praeparatum improves anxiety in mice by inhibiting HPA axis hyperactivity and modulating gut microbiota. (November 2022) - Yang, Qixin; Tian, Linhua; Li, Shuyu; Huo, Jinhai; Jiang, Yuanyuan; Chen, Liyan; Wang, Weiming
Graphical abstract: Highlights: SSP increased the desire of anxious mice to explore in elevated plus maze and the open field. SSP exerts improved anxiety effects in mice by inhibiting HPA axis hyperactivity. SSP decreased the levels of IL-1β, IL-6 and TNF-α in anxious mice. SSP modulated the unbalanced gut microbiota in anxious mice. Abstract: Semen Sojae Praeparatum (SSP) is a functional food made from fermented black soybeans used in folk medicine to treat psychiatric diseases. This study aimed to evaluate whether SSP affects anxiety and explain the improved anxiety mechanism of SSP. We found that SSP increased the exploratory desire of anxiety anxious mice in behavioral experiments, reduced cytokine (IL-1β, IL-6, and TNF-α) release in serum, dose-dependently decreased the protein and mRNA levels of neuronal nitric oxide synthase (nNOS), corticotropin-releasing factor (CRF), and decreased corticosterone concentrations downstream of the HPA axis. Additionally, SSP ameliorated intestinal disorders in mice by reducing the Firmicutes/Bacteroidetes ratio and increasing the abundance of Bacteroidota, Muribaculaceae, and Bacillus . These results demonstrate that SSP improved anxiety effects linked to regulation of HPA axis hyperactivity and gut microbiota composition.